The Weather Factory: Alan C. Burton and Military Research at the University of Western Ontario, 1945-70 - Wiseman, Matthew (Scientia Canadensis, 2023)
This article examines the impact of military funding on the career of Dr Alan C. Burton (1904–79), who is widely remembered as a founding father of modern biophysics. Burton performed military research for the Canadian armed services during the earliest decades of the Cold War, securing funding and pursuing opportunities that advanced his career in medical science. Central to his military-sponsored research was a special climatic laboratory at the University of Western Ontario dubbed the Weather Factory, which enabled a long-running experimental research program on cold and the human body. Military sponsorship enabled the research that influenced Burton’s professional trajectory from mathematician and physicist to biologist, and thus played an important role in his development as a biophysicist and interdisciplinary health scientist in mid-century Canada.